Effect of bitumen and migrated oil on hydrocarbon generation kinetic parameters derived from Rock-Eval pyrolysis. (18th October 2019) - Alizadeh, Bahram; Seyedali, Seyed Rasoul; Sarafdokht, Hashem
Abstract: Thermally immature whole rock and related bitumen-extracted samples were pyrolyzed. Investigating the influence of high molecular weight hydrocarbons and degradation products of non-hydrocarbon constituents of bitumen and associated migrated oil (i.e. resins and asphaltenes) on petroleum generation kinetic parameters derived from Rock-Eval pyrolysis is the main aim of this study. Based on the optimized kinetic parameters, frequency factor values of the bitumen-free samples show an obvious increase compared to whole rocks, while the range of activation energies for them is narrower. On the other hand, the predicted geological temperatures of the onset (TR 10%) and the peak hydrocarbon generation (geological Tmax ) from the whole rocks are generally lower than the corresponding extracted samples. In other words, the whole rock samples underestimate the petroleum formation temperatures. Thus, the results of this study suggest the extraction of bitumen prior to Rock-Eval pyrolysis in order to obtain precise kinetic parameters for the source rocks bearing a large amounts of heavy bitumen or migrated oil.